2020
DOI: 10.1111/ene.14330
|View full text |Cite
|
Sign up to set email alerts
|

Early successful reperfusion after endovascular therapy reduces malignant middle cerebral artery infarction occurrence in young patients with large diffusion‐weighted imaging lesions

Abstract: Background and purpose Malignant middle cerebral artery infarction (MMI) is a severe complication of acute ischaemic stroke (AIS). The aim of our study was to assess whether successful reperfusion after endovascular therapy (EVT) in AIS with clinical and imaging predictors of MMI decreased its occurrence. Methods Data were collected between January 2014 and July 2018 in a monocentric prospective AIS registry of patients treated with EVT. Patients selected were <65 years old with severe anterior circulation AIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…In contrast to our findings, Tracol et al demonstrated that time to MT and infarct volume were independent predictors of MCE, while TICI score was not [33]. In Sabben et al, patients undergoing MT were also analyzed for predictors of MCE, patients with TICI scores ≥ 2B developed significantly less MCE (p < 0.05) [34]. In another retrospective series of 98 patients (35.7% MCE), neither increased clot retrieval attempts nor TICI score predicted MCE [35].…”
Section: Procedural Variables In Mt Patientscontrasting
confidence: 99%
“…In contrast to our findings, Tracol et al demonstrated that time to MT and infarct volume were independent predictors of MCE, while TICI score was not [33]. In Sabben et al, patients undergoing MT were also analyzed for predictors of MCE, patients with TICI scores ≥ 2B developed significantly less MCE (p < 0.05) [34]. In another retrospective series of 98 patients (35.7% MCE), neither increased clot retrieval attempts nor TICI score predicted MCE [35].…”
Section: Procedural Variables In Mt Patientscontrasting
confidence: 99%
“…Whereas first studies mainly focused on patients with no or only small infarct demarcation, recent randomized controlled trials provided evidence for beneficial effects of EVT also in the situation of an already existing relevant infarct demarcation [7][8][9]. Along with an increasing implementation of EVT in acute stroke management, data on individual courses emerging from the real-world setting indicated a decreased rate of space-occupying brain infarction [10][11][12], in conjunction with a reduced rate of DHC [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) is highly sensitive to acute ischemia and has been widely adopted in detecting early ischemic damage (1,2). However, the DWI lesion suffers from graded tissue injury (3)(4)(5). Specifically, a portion of the DWI lesion is potentially reversible with early reperfusion, even occasionally in cases with large DWI lesions (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%